Quantitative analysis of the performance improvement of the surrounding rock mass by applying a prestressed bolt system - Xuxu Yang; Hongyun Xue; Junwei Guo; Mingming Zhang (Scientific Reports)
Abstract Prestressed bolts have been increasingly used in underground engineering as a practical solution to control the instability of surrounding rock masses. However, blindly increasing the density of prestressed bolt has limited influence on the performance improvement of tunnel surrounding rock mass. Therefore, the accurate design of the parameters of the prestressed bolt in the support system is a significant method to improve the bearing capacity of the tunnel surrounding rock. To solve this problem, we carried out large-scale physical model tests of anchored rock block with nonpersistent joints. An innovative method for prestressed bolt simulation is proposed by using the code independently developed in PFC3D, and then a series of numerical model compression tests of anchored rock block with different prestressed bolt densities are extended based on physical model tests. The results indicate that the original failure mode of the rock block is not changed by adding bolt. And an increase in the density of the prestressed bolt leads to a change in the anchoring mechanism of the rock block. When the density of prestressed bolt is low, the upper load is mainly borne by rock block, and the increase of the density of bolt will mobilize more intact rock to participate in the load. When the density of prestressed bolt increases to a certain extent, the upper load is mainly borne by the prestressed bolt. And the performance improvement of prestressed bolt to rock block is limited. When the prestress and density of bolt reach a certain degree, the strength of rock mass is only increased by 10% when the prestress and density of bolt are doubled. The increase of the density of prestressed bolt makes the deformation of rock block more stable, and the ɛ3/ɛ1 ratio of the anchored rock block is always less than 1.0. The research results have important guiding significance for tunnel surrounding rock masses support design.